THE AESTHETICS OF RENTENG DANCE - Anak Agung Gde Agung Indrawan; I Ketut Sariada; Ni Made Arshiniwati (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: The Renteng dance in Saren I Hamlet, Nusa Penida, Klungkung, Bali has a very simple form. As a work of art, this dance does not explicitly show beautiful power, but implicitly, it can create beauty based on the qualities it has. This research aims to reveal, describe and understand the aesthetics of the Renteng dance in Saren I Hamlet, Nusa Penida, Klungkung, Bali. Research methods: The method used in this research is qualitative utilizing data collection techniques in the form of observation and documentation. The results of this research show that the aesthetics of the Renteng dance in Saren I Hamlet, Nusa Penida, Klungkung, Bali can be seen through unity, diversity, and intensity. Findings: The aesthetics contained in the Renteng dance through its three beautiful characteristics illustrate that no matter how simple the dance is, it will still create an aesthetic experience. The aesthetic experience of this dance can be seen through the unity of the elements or forming elements which are intertwined as a whole and single, and have a strong detailed effect that is carried out repetitively to create harmony. Implications: The aesthetics contained in the Renteng dance in Saren I Hamlet, Nusa Penida, Klungkung, Bali, through the three characteristics of beauty that have been discussed, illustrate that no matter how simple or simple the dance is, it will still create an aesthetic experience. The aesthetic experience of the Renteng dance in Saren I Hamlet, Nusa Penida, Klungkung, Bali can be seen through the unity of the elements or forming elements which are woven wholly and singly, and have a strong detailed effect which is carried out repetitively, thus creating harmony.